Unit cost repositories for health program planning and evaluation: a report on research in practice with lessons learned - Lori A. Bollinger; Joseph Corlis; Regina Ombam; Steven Forsythe; Stephen C. Resch (BMC, 2023)
Abstract Background Most low- and middle-income countries have limited access to cost data that meets the needs of health policy-makers and researchers in health intervention areas including HIV, tuberculosis, and immunization. Unit cost repositories (UCRs)-searchable databases that systematically codify evidence from costing studies-have been developed to reduce the effort required to access and use existing costing information. These repositories serve as public resources and standard references, which can improve the consistency and quality of resource needs projections used for strategic planning and resource mobilization. UCRs also enable analysis of cost determinants and more informed imputation of missing cost data. This report examines our experiences developing and using seven UCRs (two global, five country-level) for cost projection and research purposes. Discussion We identify advances, challenges, enablers, and lessons learned that might inform future work related to UCRs. Our lessons learned include: (1) UCRs do not replace the need for costing expertise; (2) tradeoffs are required between the degree of data complexity and the useability of the UCR; (3) streamlining data extraction makes populating the UCR with new data easier; (4) immediate reporting and planning needs often drive stakeholder interest in cost data; (5) developing and maintaining UCRs requires dedicated staff time; (6) matching decision-maker needs with appropriate cost data can be challenging; (7) UCRs must have data quality control systems; (8) data in UCRs can become obsolete; and (9) there is often a time lag between the identification of a cost and its inclusion in UCRs. Conclusions UCRs have the potential to be a valuable public good if kept up-to-date with active quality control and adequate support available to end-users. Global UCR collaboration networks and greater control by local stakeholders over global UCRs may increase active, sustained use of global repositories and yield higher quality results for strategic planning and resource mobilization.